Ideological belief bias with political syllogisms. (2nd April 2020) - Calvillo, Dustin P.; Swan, Alexander B.; Rutchick, Abraham M.
Abstract: The belief bias in reasoning occurs when individuals are more willing to accept conclusions that are consistent with their beliefs than conclusions that are inconsistent. The present study examined a belief bias in syllogisms containing political content. In two experiments, participants judged whether conclusions were valid, completed political ideology measures, and completed a cognitive reflection test. The conclusions varied in validity and in their political ideology (conservative or liberal). Participants were sensitive to syllogisms' validity and conservatism. Overall, they showed a liberal bias, accepting more liberal than conservative conclusions. Furthermore, conservative participants accepted more conservative conclusions than liberal conclusions, whereas liberal participants showed the opposite pattern. Cognitive reflection did not magnify this effect as predicted by a motivated system 2 reasoning account of motivated ideological reasoning. These results suggest that people with different ideologies may accept different conclusions from the same evidence.